Crystal structures of polyamide 6 at the interphase and around carbon fiber and mechanical properties of their composites. (9th May 2023) - Uematsu, Hideyuki; Nishimura, Shunya; Yamaguchi, Ayaka; Nishimura, Fumihiro; Sugihara, Shinji; Sugiura, Naoki; Ishikawa, Takeshi; Hayashi, Takahiro; Yamane, Masachika; Kawabe, Kazumasa; Ozaki, Yukihiro; Tanoue, Shuichi
Abstract: This study reports the effect of the polyamide 6 (PA6) crystal structure at the interphase and around the carbon fiber (CF) on the mechanical properties of CF-reinforced PA6 composites. The transverse tensile properties of the unidirectional composites and the four-point bending properties of the quasi-isotropic composites were investigated using three types of CFs. Raman spectra of PA6 were measured to characterize the crystal structures of PA6 at the interphase and around the CFs. The results showed that higher α-crystal (the most thermodynamically stable crystal) content of PA6 at the interphase compared to β-crystal (mesophase) and γ-crystal (thermodynamically metastable) contributed to greater transverse tensile strength of unidirectional composites. Furthermore, it was demonstrated that the flexural strength of the quasi-isotropic composites increased in the case of small variations in the distribution of each crystal structure (α-, β-, and γ-crystal structures) around the CFs. This study provides a framework for the PA6 crystals around CFs to reflect the superior properties of CFs in PA6/CF composites. Graphical abstract: Image 1 Highlights: Sizing agents on the carbon fiber surface affect the crystal formation of polyamide 6. The strength balance of polyamide 6 near carbon fiber determines the facture patterns. Crystal uniformity of polyamide 6 is a key in reinforcement degree by carbon fibers. Direct Raman analysis of fracture surface is very useful for interphase characterization.